Beneficios de la rehabilitación cardiovascular en adultos mayores con insuficiencia cardíaca tipo I. - Gicela Gabriela, Valencia Albán (2021)
ABSTRACT This research was developed under a bibliographic review modality, scientific articles were collected that complied with the topic "Benefits of cardiovascular rehabilitation in elderly adults with type I heart failure", evidencing that the application of a series of respiratory and cardiac techniques contributes to the reduction of mortality and morbidity, in those patients with an adequate physiotherapeutic treatment to reintegrate them early to their daily life activities, improving their quality of life. We obtained a database of 100 scientific articles that were subjected to an adequate process of selection and extraction of optimal articles with reliable information, and selected 35 articles in Spanish, English and Portuguese from scientific databases such as Scopus, PubMed, ProQuest, Revista Colombiana de Cardiología, published between 2011 and 2020, that included the parameters established by the PEDro scale obtaining a score greater than or equal to 6, in addition to complying with all the inclusion and exclusion criteria established in the methodology. Heart failure causes a series of problems such as dyspnea, reduced exercise tolerance, fatigue, weakness, decreased respiratory capacity, rapid or irregular heartbeat, among others, demonstrating, in the analysis of results, the benefits of an adequate and personalized respiratory physiotherapeutic treatment, helping to increase respiratory capacity, contributing to tolerance to physical activity, returning to daily work and avoiding complications and, worldwide, a significant reduction in mortality rates. KEYWORDS: HEART FAILURE / RESPIRATORY CAPACITY / DYSPNEA / CARDIAC REHABILITATION, MORTALITY, MORBIDITY. Reviewed by: Msc. ENRIQUE GUAMBO YEROVI. ENGLISH PROFESSOR CI: 0601802424